'For my descendants and myself, a nice and pleasant abode' - agency, micro-history and built environment : Buildings in Society International BISI III, Stockholm 2017 - Tagesson, Göran,; Cornell, Per,; Gardiner, Mark; Thomas, Liz,; Weikert, Katherine, (Archaeopress Archaeology, 2020)
This volume examines how people have been making, using and transforming buildings and built environments, and how buildings have been perceived, from the Byzantine period to modern times. It also considers a diversity of built constructions - including dwellings and public buildings, sheds and manor houses, and secular and sacral structures.